Changes in ambulatory knee adduction moment with lateral wedge insoles differ with respect to the natural foot progression angle. (16th April 2020) - Ulrich, Baptiste; Hoffmann, Laurent; Jolles, Brigitte M.; Favre, Julien
Abstract: Lateral wedge insoles (LWI) have been proposed to reduce the knee adduction moment (KAM) during walking; a biomechanical modification notably sought in case of medial knee osteoarthritis. However, the inter-individual inconsistency in KAM changes with LWI limits their therapeutic use. Although the foot progression angle (FPA) has been frequently discussed in KAM modifications literature, there is a lack of data regarding a possible relationship between this gait measure and changes in KAM with LWI. This study aimed to test if KAM changes with LWI differ with respect to the natural FPA and to compare KAM-related variables between individuals walking with smaller and larger natural FPA. Twenty-two healthy participants (14 males, 24 ± 3 years, 22.7 ± 2.7 kg/m 2 ) underwent gait analysis with and without LWI. They were divided into two groups based on their natural FPA, and changes in KAM 1st peak, KAM impulse, and KAM-related variables were compared between groups. KAM 1st peak and impulse decreased with LWI in the smaller natural FPA group (p ≤ 0.006), while only KAM impulse decreased in the larger natural FPA group (p < 0.001). The difference in KAM 1st peak changes was explained by a less reduced lever arm in participants walking with larger natural FPA. In conclusion, this study brought new insight into the variability in KAM response to LWI. If the findings are confirmed in patients with medial knee osteoarthritis, the FPA could become a simple measure to help identify the patients more likely to reduce their KAM with LWI.